Comparative genomics study of Staphylococcus aureus isolated from cattle and humans reveals virulence patterns exclusively associated with bovine clinical mastitis strains - Rodrigues, Romário Alves; Pizauro, Lucas José Luduverio; Varani, Alessandro de Mello; de Almeida, Camila Chioda; Silva, Saura Rodrigues; Cardozo, Marita Vedovelli; MacInnes, Janet I.; Kropinski, Andrew M.; Melo, Poliana de Castro; Ávila, Fernando Antonio (Frontiers in Microbiology, 2022)
Staphylococcus aureus causes nosocomial and intramammary infections in humans and cattle, respectively. A large number of virulence factors are thought to play important roles in the pathogenesis of this bacterium. Currently, genome-wide and data-analysis studies are being used to better understand its epidemiology. In this study, we conducted a genome wide comparison and phylogenomic analyses of S. aureus to find specific virulence patterns associated with clinical and subclinical mastitis strains in cattle and compare them with those of human origin. The presence/absence of key virulence factors such as adhesin, biofilm, antimicrobial resistance, and toxin genes, as well as the phylogeny and sequence type of the isolates were evaluated. A total of 248 genomes (27 clinical mastitis, 43 subclinical mastitis, 21 milk, 53 skin-related abscesses, 49 skin infections, and 55 pus from cellulitis) isolated from 32 countries were evaluated. We found that the cflA, fnbA, ebpS, spa, sdrC, coa, emp, vWF, atl, sasH, sasA, and sasF adhesion genes, as well as the aur, hglA, hglB, and hglC toxin genes were highly associated in clinical mastitis strains. The strains had diverse genetic origins (72 protein A and 48 sequence types with ST97, ST8 and ST152 being frequent in isolates from clinical mastitis, abscess, and skin infection, respectively). Further, our phylogenomic analyses suggested that zoonotic and/or zooanthroponotic transmission may have occurred. These findings contribute to a better understanding of S. aureus epidemiology and the relationships between adhesion mechanisms, biofilm formation, antimicrobial resistance, and toxins and could aid in the development of improved vaccines and strain genotyping methods.